Biomimetic ZnO for Dye-Sensitized Solar Cells - Orozco-Messana, Javier (Nanomaterials (Basel), 2020)
A research study on the application of biomimetic ZnO (from eggshell membranes) as photoanodes in dye-sensitized solar cells (DSSCs) is presented. Biomimetic ZnO powder was produced and characterized. Its surface area, crystallinity, and morphology were analyzed and compared to commercial ZnO. Then, solar cells with and without dye were assembled using both the biomimetic and commercial oxides. On the dye-less cell, the oxide assumes the role of the photon absorber, while in the dye-sensitized cells, the oxide’s major function is the separation of the electron-hole pair and conduction of the electric charges formed. The characterization of the oxides showed that the biomimetic synthesis produced ZnO with a larger surface area, smaller crystallite size, and larger light absorption, possibly due to crystalline defects. SEM analysis on biomimetic ZnO revealed a tubular microstructure formed by nanocrystals, instead of the commercial powder showing spherical particles.